Diagnostic medical parasitology - Garcia, Lynne Shore
Diagnostic Medical Parasitology covers all aspects of human medical parasitology and provides detailed, comprehensive, relevant diagnostic methods in one volume. The new edition incorporates newly recognized parasites, discusses new and improved diagnostic methods, and covers relevant regulatory requirements and has expanded sections detailing artifact material and histological diagnosis, supplemented with color images throughout the text